2023
DOI: 10.1001/jama.2023.10875
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-Derived “Weekend Warrior” Physical Activity and Incident Cardiovascular Disease

Abstract: ImportanceGuidelines recommend 150 minutes or more of moderate to vigorous physical activity (MVPA) per week for overall health benefit, but the relative effects of concentrated vs more evenly distributed activity are unclear.ObjectiveTo examine associations between an accelerometer-derived “weekend warrior” pattern (ie, most MVPA achieved over 1-2 days) vs MVPA spread more evenly with risk of incident cardiovascular events.Design, Setting, and ParticipantsRetrospective analysis of UK Biobank cohort study part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 15 publications
0
28
0
2
Order By: Relevance
“…In this issue of JAMA, Khurshid et al 9 examined the associations between an accelerometer-derived "weekend warrior" pattern in which 150 minutes or more of MVPA with 50% or more of total MVPA was achieved in 1 to 2 days per week vs 150 minutes or more of MVPA but not meeting the weekend warrior definition, with risk of incident atrial fibrillation, myocardial infarction, heart failure, and stroke among 89 573 participants in the UK Biobank. Compared with inactive adults, those with either pattern of physical activity accumulation showed similar, significantly reduced risk of all cardiovascular disease outcomes.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In this issue of JAMA, Khurshid et al 9 examined the associations between an accelerometer-derived "weekend warrior" pattern in which 150 minutes or more of MVPA with 50% or more of total MVPA was achieved in 1 to 2 days per week vs 150 minutes or more of MVPA but not meeting the weekend warrior definition, with risk of incident atrial fibrillation, myocardial infarction, heart failure, and stroke among 89 573 participants in the UK Biobank. Compared with inactive adults, those with either pattern of physical activity accumulation showed similar, significantly reduced risk of all cardiovascular disease outcomes.…”
mentioning
confidence: 94%
“…Compared with inactive adults, those with either pattern of physical activity accumulation showed similar, significantly reduced risk of all cardiovascular disease outcomes. 9 These results highlight the flexibility with which physical activity can be accumulated to achieve health benefits, which should further enhance opportunities for engagement for large segments of the population.…”
mentioning
confidence: 99%
“…They found that compared to those who were inactive, participants who were insufficiently active, regularly active or “weekend warriors” all had a more favorable vascular health, with no difference between the regularly active or the “weekend warriors.” When looking at downstream cardiovascular events in the UK Biobank study, Kurshid et al 7 . similarly found that those who completed ≥150 min/week through being “active regularly” or “weekend warriors” both had lower risk of cardiovascular events compared to those who were inactive 7 . However, grouping people based on combinations of duration, intensity and frequency of PA makes it difficult to isolate the effect of PA pattern from overall PA volume, of which we know is beneficially associated with vascular health.…”
Section: Introductionmentioning
confidence: 99%
“…Nun wurde erstmals in einer sehr großen Untersuchung mit objektiver Messung der Aktivität mittels eines Akzelerometers ein ähnlich großer Gesundheitseffekt bezüglich einer großen Bandbreite kardiovaskulärer Endpunkte, einschließlich der Mortalität, gezeigt. Es machte keinen Unterschied, ob die Sporteinheiten über die Woche verteilt oder konzentriert auf das Wochenende stattfanden [4].…”
unclassified